METHODS OF INFORMATION SECURITY IN WIRELESS NETWORKS - Shinasilova, F. (Scientific Journal of Astana IT University, 2020)
The development of information technology sets the task of improving the reliability of computer networks. To study the security of networks, it is necessary to study the creation of network protocols, network architectures, and ways to strengthen security when transmitting information resources over a network. Network attacks, failures, and the failure of network devices are key factors affecting the security of information transmission in wireless networks.This article discusses methods for protecting information in wireless networks, including standards for authentication, encryption, and security. There are several security standards, but this article describes the effectiveness of those standards and the key principles used in those standards. It also outlines the principles of standards that ensure the confidentiality and integrity of data. That is, the TKIP protocol generates a new secret key for each packet of data transmitted, and one static WEP key is exchanged for about 500 billion possible keys. It can be used to encrypt this data set. The key generation mechanism has been modified. It consists of three components: a 128-bit Basic Key (TC), a packet number (TSC) and a MAC address of the carrier. The TKIP also uses a 48-bit initialization vector. It is used to prevent repeated use of vector IV. The TKIP algorithm uses a 48-bit (TSC) packet calculation. It keeps increasing. Well, the new 16-bit TSC IV is introduced (Figure 4). Thus, a mechanism is created that can block attacks.